Does Gender Diversity on Board Promote Corporate Social Responsibility? An Empirical Analysis of Sustainable Development Goals - Amit Kumar Singh; Hima Bindu Kota; Varda Sardana; Shubham Singhania (Australasian Accounting, Business and Finance Journal, 2021)
Recent regulatory changes in India require the firms to improve the appointment of female directors on corporate boards, and it is believed that such a regulation would prove to be a boon in terms of strategic decision making. The Board Capital Theory advocates that the appointment of women directors on board shall enhance various dimensions of the board capital breadth and help in better decision making. With growing consciousness for sustainable practices throughout the globe, it is pertinent to see whether the gender diverse boards can promote corporate social responsibility and create a business case for their upsurge, as it would give room for policy implications. This study investigates the impact of gender diverse boards on promoting corporate social responsibility, using multivariate regression with a sample of NIFTY 50 Index for the period 2014-2019. The study found insignificant positive relation among gender-diverse boards and sustainability. To check for the robustness of the study, we have used two diversity indices, Blau & Shannon index, to supplement our results.
Keywords: Gender Diversity; Sustainability; Corporate Governance; NIFTY 50 Companies.